Trends and Developments in Greenwashing Practices and Sustainability Accounting: A Bibliometric Analysis - Shodiq, Muhammad Ja'far (INDONESIAN JOURNAL OF SUSTAINABILITY, 2025)
This study aims to map the trends, developments, and patterns of research in greenwashing and sustainability accounting practices using a bibliometric analysis approach. Research data were obtained from the Scopus database with a publication period from 2007 to 2025. This study uses bibliometric analysis assisted by R-Packages software and Web Interface Biblioshiny. This study identifies the development of greenwashing and sustainability accounting practices through an analysis of annual publication trends. In practice, greenwashing and sustainability accounting are the same form but have different implications. This study is driven by the need to understand the greenwashing practice trends and developments in sustainability accounting, which make important contributions to the development of global business. The results of the study show an increase in global interest in the issue of greenwashing and sustainability accounting, with a dominant contribution to research from developed countries such as China, the United States, the United Kingdom, Italy, and India. The gap in research participation between developed and developing countries indicates the need for a more inclusive and collaborative approach. The results also show the importance of international collaboration, consumer education, and a clear regulatory framework to prevent greenwashing practices and support the implementation of transparent and accountable sustainability accounting. This research is expected to be a basis for further research and more appropriate policy making in efforts to encourage global sustainability through sustainable development and a green economy.